Frequency of Ophthalmological Disorders Among Soldiers on Operational Duty at the Ophthalmology Unit of the Medical Surgical Center of Bamako’s Arms - Traore, O. Y.; Kamissoko, D.; Sanogo, S.; Traore, Y. M.; Kouyate, K.; Sissoko, M.; Sidibe, M K; Kone, A. D.; Diarra, M.; Traore, K.; et al. (European Journal of Applied Sciences, 2025)
Introduction : The aim of our study was to determine the frequency of ocular disorders among military personnel on operational duty at the CMCAB Ophthalmology Unit, in order to ensure their adequate management and an improvement in their operational capacity. Patients and method : This was a cross-sectional, retrospective study conducted between January 1 and March 31, 2024 at the Army medical-surgical center in Bamako/Mali. Results : A total of 264 patients were examined during the study. The distribution of patients by rank was as follows : non commissioned officers were the most frequent, accounting for 36.4% of cases, followed by non-commissioned officers for 34.1%. Visual function abnormalities were the most frequent. These were mainly ametropia, accounting for 81.9% of cases. Discussion : Studies on the frequency of ocular disorders in the military are few and far between, but we can cite that of DIALLO et al. KOKI G and colleagues found a clear predominance of functional pathologies, particularly ametropia, with a frequency of 22.17%, 37.4% (56.4% for our study). Conclusion : The ophthalmological conditions encountered are numerous and multiple in the military personnel seen at the Army medical-surgical center in Bamako/Mali. Identifying them in this study will enable us to prevent and manage them, and reduce their complications.